Implementasi Algoritma Elliptic Curve Cryptography (ECC) Untuk Penyandian Pesan Pada Aplikasi Chatting Client Server Berbasis Desktop - Damanik, Putri S E (STMIK Budi Darma, 2019)
The problem of security on computers is the most important issue in the current era of information technology. Many cyber crimes that occur one of which is related to data manipulation on the network. The most important problem with computer security is the security of the data that is sent. Examples of data that really need to be secured are messages in chat applications. In addition to preventing information from being read by other parties, encoding of messages greatly enables the effectiveness of sending confidential information. One type of asymmetric algorithm that has 2 different keys for encryption and decryption in the method of hiding messages (Cryptography) where the sender of the message first uses the public key (public key) to encode the message, and to decrypt the encrypted message the recipient will use a secret key (private key ). The Elliptic Curve Cryptography algorithm is quite complicated in its calculations, because the calculations are different from ordinary calculations.